Pencegahan Stunting sebagai Peran Nutrisi dalam Seribu Hari Pertama Kehidupan di Desa Cilentung Kecamatan Pulosari Kabupaten Pandeglang - Herry Octa Winarto; April Laksana; Rica Anggraini; Afghan Dzikri Muhabba; Agung Sumantri (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
In Indonesia, stunting is a health condition, stunting can occur in children in the first 1000 days of birth. Cilentung Village, Pulosari District, Pandeglang Regency is the village with the highest stunting rate in Pulosari District compared to 8 other villages. KKM 53 UNIBA held this event as a form of community service as well as a work program in the health sector. carrying the theme Stunting Prevention as the Role of Nutrition in the First Thousand Days of Life, targeting 35 young/pregnant mothers from 10 villages in 16 RT/RW in Cilentung village. In the Cilentung Village Area, Pulosari District, stunting prevention is carried out through several strategies, including monitoring socialization activities regarding stunting, encouraging clean and healthy living, and providing additional food. In this case, repeated infections and chronic malnutrition in the first 1000 days of life are the causes of children's growth and development failure, which is characterized by height or body length below the 2020 Anthropometric Standards, although not all short children experience this, which health professionals count. children who experience stunting